Investigating cooperativity across adenosine A3 receptor homo- and hetero-oligomers - Groenewoud, N.J.A. (2019)
Oligomerisation of receptors is the process whereby two or more receptors associate to form a new functional unit which can have distinct characteristics. These characteristics include changes in trafficking of the receptor, changes in signalling, and changes in ligand binding. The adenosine and β-adrenoceptor families are two class A GPCR families and some receptors from this family are reported to form oligomers both within their family as well as with other class A GPCRs.